Mathematical model of Reiner-Philippoff embedded with Al2O3 and Cu particles over a shrinking sheet with mixed convection and mass flux effect - Mohd Kasim, Abdul Rahman; Nordin, Nur Syahidah; Mohammed Al-Sharifi, Hussein Ali; Waini, Iskandar; Mokhtar, Masyfu’ah; Romli, Mohd Fakhizan; Samsudin, Dafrizal; Adytia, Didit (Penerbit Akademia Baru, 2023)
The investigation on the Reiner–Philippoff fluid model embedded with two different nanoparticles (Al2O3 and Cu) over a shrinking sheet is carried out. The Tiwari and Das model are applied in the study covering the continuity, momentum, energy equations, and Reiner-Philippoff relation. The flow studied also considers the mixed convection and mass flux influences. The respective equations are first transformed into ordinary differential equation form using the similarity transformation before performing the computation work using the bvp4c function in MATLAB. The present model is identical to the established model in special cases, and then a direct comparative study is executed to verify the current model. The results for respective problems are presented in tabular and graphical form. It is perceived that the presence of nanoparticles affects the fluid characteristic significantly.